Characterization of Clostridium difficile Spores Lacking Either SpoVAC or Dipicolinic Acid Synthetase - Donnelly, M. Lauren (J Bacteriol, 2016)
The spore-forming obligate anaerobe Clostridium difficile is a leading cause of antibiotic-associated diarrhea around the world. In order for C. difficile to cause infection, its metabolically dormant spores must germinate in the gastrointestinal tract. During germination, spores degrade their protective cortex peptidoglycan layers, release dipicolinic acid (DPA), and hydrate their cores. In C. difficile, cortex hydrolysis is necessary for DPA release, whereas in Bacillus subtilis, DPA release is necessary for cortex hydrolysis. Given this difference, we tested whether DPA synthesis and/or release was required for C. difficile spore germination by constructing mutations in either spoVAC or dpaAB, which encode an ion channel predicted to transport DPA into the forespore and the enzyme complex predicted to synthesize DPA, respectively. C. difficile spoVAC and dpaAB mutant spores lacked DPA but could be stably purified and were more hydrated than wild-type spores; in contrast, B. subtilis spoVAC and dpaAB mutant spores were unstable. Although C. difficile spoVAC and dpaAB mutant spores exhibited wild-type germination responses, they were more readily killed by wet heat. Cortex hydrolysis was not affected by this treatment, indicating that wet heat inhibits a stage downstream of this event. Interestingly, C. difficile spoVAC mutant spores were significantly more sensitive to heat treatment than dpaAB mutant spores, indicating that SpoVAC plays additional roles in conferring heat resistance. Taken together, our results demonstrate that SpoVAC and DPA synthetase control C. difficile spore resistance and reveal differential requirements for these proteins among the Firmicutes. IMPORTANCE Clostridium difficile is a spore-forming obligate anaerobe that causes ∼500,000 infections per year in the United States. Although spore germination is essential for C. difficile to cause disease, the factors required for this process have been only partially characterized. This study describes the roles of two factors, DpaAB and SpoVAC, which control the synthesis and release of dipicolinic acid (DPA), respectively, from bacterial spores. Previous studies of these proteins in other spore-forming organisms indicated that they are differentially required for spore formation, germination, and resistance. We now show that the proteins are dispensable for C. difficile spore formation and germination but are necessary for heat resistance. Thus, our study further highlights the diverse functions of DpaAB and SpoVAC in spore-forming organisms.